The Relationship between Parental Education and Occupation Levels on Biology Science Learning Outcomes - Aprima, Aprima (RADINKA JAYA UTAMA PUBLISHER, 2023)
This research aims to determine the relationship between educational level and parental employment on the learning outcomes of class VII students at SMP N 4 Batang Anai, Padang Pariaman Regency. This type of research is descriptive correlational. The population in this study were all class VII students of SMP N 4 Batang Anai, Padang Pariaman Regency. The research results between educational level and biology science learning outcomes are (tcount 5.175 with a significance value of 0.000 < 0.05) and the contribution amount is 17.8% of the results, showing that there is a significant relationship. Parental work and biology science learning outcomes are (t-count 2.477 with a significance value of 0.015 < 0.05) with a contribution amount of 4.7%. The results show that there is no significant relationship. The level of education and employment of parents with the results of studying biology science is (Fcount 14.176 with a significance value of 0.000 < 0.05) and the contribution amount is 18.7%, The results show that there is a significant relationship. It can be concluded that parental occupation is significantly related to biological science learning outcomes, as well as parental education is significantly related to biological science learning outcomes, and parental education and employment are significantly related to biology science learning outcomes for class VII students at SMP N 4 Batang Anai Regency. Padang Pariaman.